Time-based autonomous orbit control laws using a low-thrust system to maintain orbit configuration of satellite constellations - Soung Sub Lee (Ain Shams Engineering Journal, 2025)
This study proposes a time-based automated orbit control law for low-thrust systems, along with the application of an orbit tube to maintain the orbit configuration of a specific satellite constellation. The orbit configuration is currently designed such that the satellite group flies on a single ground track using the recently developed RGT-Walker (Repeating Ground Track and Walker) method, and the orbit configuration cannot be maintained because of the effects of perturbation. This study solves this problem by maintaining the orbit configuration within a specific orbital tube by a time-based autonomous control technique using only semi-major axis. These efforts contribute to significantly reducing the workload of mission operations, such as the simplification of complex sensor operations and the implementation of an automated orbit control command system through periodic and identical repeating ground track operations of the satellite constellation. In addition, this study provides diverse and meaningful experimental simulation results, including revisit performance evaluation, sensor operation plan, and fuel consumption analysis. In particular, the proposed on–off autonomous control law is verified to significantly reduce fuel consumption in low-thrust systems compared to conventional control methods.